Do controle social ao desvio de conduta: uma análise do comportamento policial militar, em Belo Horizonte - Fernando Xavier Pereira (2016)
The state organization designed to protect citizens appears to be, in several situations, the first to violate their rights. In addition, the permanence of violent patterns of police action indicates that the police relationship with a large part of the population and indisputably marked by the violation of the rights of police officers. And from this question, this research sought to understand the misconduct of police conduct and, consequently, the treatment given by the military police Internal Affairs of Minas Gerais State to the complaints that are filed in that organ, interpreting the findings according to the national and international literature that explain the Phenomena of misconduct of police in general.